2011
DOI: 10.1177/0143831x11424768
|View full text |Cite
|
Sign up to set email alerts
|

Employee turnover, HRM and institutional contexts

Abstract: Literature on comparative capitalism remains divided between approaches founded on stylized case study evidence and descriptions of broad trends, and those that focus on macro data. In contrast, this study explores the relevance of Amable's approach to understanding differences in employment relations practice, based on firm-level micro data. The article examines employeeemployer interdependence (including turnover rates) in different categories of economy as classified by Amable. The findings confirm that exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Since Tsui et al's (2007) article bemoaned the lack of comparative studies based on other than cultural factors, there has been a burst of activity. And there does indeed seem to be evidence that institutional factors matter in recruitment and selection (Wood, Brewster, Demirbag and Brookes 2014), training (Goergen et al 2012), employment relations , flexible working practices (Richbell, Brookes, Brewster and Wood 2011), turnover (Croucher, Wood, Brewster and Brookes 2012) and downsizing (Wood, Goergen and Brewster 2013). It is also clear that these differences are relatively stable and continue over decades (Mayrhofer, Brewster, Morley and Ledolter 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Since Tsui et al's (2007) article bemoaned the lack of comparative studies based on other than cultural factors, there has been a burst of activity. And there does indeed seem to be evidence that institutional factors matter in recruitment and selection (Wood, Brewster, Demirbag and Brookes 2014), training (Goergen et al 2012), employment relations , flexible working practices (Richbell, Brookes, Brewster and Wood 2011), turnover (Croucher, Wood, Brewster and Brookes 2012) and downsizing (Wood, Goergen and Brewster 2013). It is also clear that these differences are relatively stable and continue over decades (Mayrhofer, Brewster, Morley and Ledolter 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, despite increasing levels of internationalization and attendant pressures to de-regulate economies, in general, and employment regulations, in particular, comparative institutional analysis (CIA) has shown how patterns of economic coordination continue to differ between countries (Hotho, 2014;Psychogios and Wood, 2010;Szamosi et al, 2010), supporting the view that contrasting institutional settings lead to different kinds of advantages to firms (Allen and Whitely, 2012;Schneider and Paunescu, 2012). More specifically, CIA analyses have shown how employment legislation can shape employers' investments in particular employee skills (Harcourt and Wood, 2007), how institutionalized forms of worker voice can lower employee turnover rates (Croucher et al, 2012) and collective redundancies (Brewster et al, 2015), and how institutions shape organizations' use of external training providers (Walker et al, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…Apart from showing clear distinctions between countries on HRM, studies from this project, and from other sources, have identified clear differences between countries: in responses to the ageing workforce in the UK and Germany (Müller-Camen, Croucher, Flynn & Schröder, 2011); in the professionalism of the HRM function between the UK and other European Countries (Farndale, 2005), in compensation practices in ten countries across three continents (Lowe, Milliman, De Cieri, & Dowling, 2002), related differences in financial participation (Pendeleton, Poutsma, Ligthart, & Brewster, 2013), differences in training (Goergen, Brewster, Wood, & Wilkinson, 2012), management development systems across Europe (Mabey & Ramirez, 2004), employee turnover in the USA and nine European countries (Croucher, Wood, Brewster, & Brookes, 2012), and downsizing in 16 different countries (Goergen, Brewster, & Wood, 2013). …”
Section: The Role Of Contextmentioning
confidence: 99%